Expertise doordacht: reflectie via klimaatanalyse - Kosolosky, Laszlo (Ethiek en Maatschappij, 2010)
This paper analyses four theoretical problems concerning the notion of expertise and tries to formulate answers by scrutinizing these problems in light of scientific practice. The focus will be on the problems arising from the interference of experts in democratic decision making. I formulate my answers by referring to the Review-process of the Intergovernmental Panel on Climate Change (IPCC). Analysing how expertise influences this particular scientific practice is an example of how social-epistemological research is done and has to be done.